Development and quality analysis of protein enriched instant soup mix : - Manvilay, Saphaothong (Trường Đại học Cần Thơ, 2019)
This research also carried out method cooking and the type of packaging of soup powder. The “Tra” fish and moringa leaf were prepared by drying using a cabinet dryer at constant airflow rate and different temperatures (60, 70 and 80oC) or freeze-drier (especially for “Tra” fish) with varying time (from 12 to 60 hours). The chemical-physical characteristics and sensory value of the products were analyzed.